Human papillomavirus circulating tumor DNA: a diagnostic tool in squamous cell carcinoma of unknown primary—a pilot study - Kais, Amani; Santiago, Stell Patadji; Han, Peng Cheng; Clump, David A.; Stokes, William A.; Fancy, Tanya; Cui, Ruifeng; Martin, Elizabeth; Turner, Meghan T. (Frontiers in Oncology, 2024)
Introduction: Neck mass is the most common presentation of human papillomavirus-related (HPV-related) oropharyngeal squamous cell carcinoma (OPSCC). Recently, circulating tumor HPV-DNA (ctHPVDNA) assays have been developed to detect active OPSCC. This pilot study investigates the diagnostic accuracy of ctHPVDNA in establishing HPV-status for known vs.unknown OPSCC presenting as a neck mass.Methods: Single-institution, pilot study of all patients with OPSCC presenting as a neck mass between 2021-2022. The diagnostic accuracy of ctHPVDNA was compared to standard diagnostic procedures used to obtain HPV status in the ASCO guideline for Squamous Cell Carcinoma of Unknown Primary (SCCUP). Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of ctHPVDNA were calculated.Results: A total of 27 patients were included; 70.4% were current or former smokers, 48.1% (N = 13) had identifiable primaries, and 51.9 % (N = 14) had SCCUP. Four patients with known primaries required operative DL biopsy to establish HPV status. Two patients with SCCUP underwent diagnostic transoral robotic surgery (TORS) to establish HPV status and localize the primary. Twelve patients underwent therapeutic TORS and neck dissection. The gold standard for HPV status was based on final histopathologic p16 or HPV-ISH staining during workup/treatment. ctHPVDNA had 95.8% sensitivity, 100% specificity, 100% PPV, and 75% NPV in predicting HPV-positive OPSCC in the whole sample. Binary logistic regression model